Review of PARS in Practice: More Resources and Strategies for Online Writing Instructors, Jessie Borgman and Casey McArdle, editors - Madeline Crozier (Journal of the Assembly for Expanded Perspectives on Learning, 2022)
The charge that “we are all online writing instructors” should resonate with any composition instructor who has taught during the Covid-19 pandemic (Borgman and McArdle 3). This exigent universal truth gives rise to the compilation of this volume. The well-timed collection builds on Borgman and McArdle’s co-authored book Personal, Accessible, Responsive, Strategic: Resources and Strategies for Online Writing Instructors, which earned the 2020 Computers and Composition Distinguished Book Award and introduced the PARS approach to online writing instruction—Personal, Accessible, Responsive, Strategic.
Keywords: JAEPL